MODERATE MAGNITUDE EARTHQUAKE SEQUENCES IN CENTRAL GREECE (FOR THE YEAR 2008) - Roumelioti, Z.; Kiratzi, A. (Bulletin of the Geological Society of Greece, 2010)
The small-to-moderate magnitude earthquake sequences offshore NE Evia island (Mantoudi, October 2008) and in central Greece, to the NW of the town of Amfiklia (December 2008) are studied in terms of their source parameters and strong shaking in nearby populated areas. Moment tensors of the strongest events of the sequences, their seismogenic faults and the distribution of slip on them are sought through the inversion of regional broadband waveforms. We then apply a forward modelling technique, which incorporates synthetic Green’s functions calculated for a 1D velocity model, previously proposed for the broader studied area, to get a first-order evaluation of the distribution of strong ground shaking around the hypocenters. The Mantoudi earthquake sequence is found to be associated to an offshore NESW trending normal fault that dips to the NW, with a considerable dextral strike-slip component. The Amfiklia earthquake sequence is related to a pure normal, E-W trending fault which dips to the south. This conclusion is drawn by both the distribution of aftershocks and the inversion process for the computation of slip on the seismogenic fault of the strongest event of the sequence (Mw5.1). Forward modelling of strong ground shaking based on event-specific moment tensor and slip distribution indicates low levels of expected ground motion in accordance with the limited observed damage.